Challenges in Group Governance : The Governance of Cross-Border Bank Subsidiaries - Frederick, W. Richard (International Finance Corporation, Washington, DC, 2017)
This publication lends itself to careful perusal as well as quick reference. An executive summary enumerates the main points, and callouts in the main text summarize the key messages of individual pages. The report provides an in-depth discussion and further detail, and text boxes, figures, and quotes add enriching perspectives. The two appendixes offer: 1) Basel Committee guidance on the governance of bank subsidiaries, and 2) a selection of recommendations from a past International Finance Corporation (IFC) publication on governance of banks in Southeastern Europe. Finally, the list of references consulted during preparation of this publication may be useful for pursuing a deeper understanding of the issues. It is important to note that this publication reflects the views of bankers, regulators, and others on a deeply complex and complicated issue and is not intended to be a comprehensive or even complete evaluation of the issues explored. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.